THE INFLUENCE OF HIGHER ORDER THINKING SKILLS, VOCABULARY MASTERY AND READING MOTIVATION ON READING COMPREHENSION ACHIEVEMENT - Titik Sholihah; Agus Widyantoro (Bajang Institute, 2021)
This research aims at finding out the influence of Higher Order Thinking Skills (HOTS), vocabulary mastery and reading motivation on reading comprehension achievement among State SMP Students in Magelang Regency. This research was an ex post facto involving three independent variables; students’ HOTS (X1), vocabulary mastery (X2), and reading motivation (X3) and one dependent variable, students’ reading comprehension achievement (Y). The sampling technique was the proportional cluster random sampling. The research instruments were three tests and a questionnaire. The kind of validity of the tests was the content validity by experts’ judgment. The construct validity of the questionnaire was measured by factor analysis. The reliability of the tests was measured by Cronbach’s Alpha with the Alpha of HOTS test is 0.768, vocabulary mastery test’s is 0.757 and the reading comprehension achievement test’s is 0.716. The reliability of the questionnaire was measured by Cronbach’s Alpha with the Alpha is 0.862. The data were analyzed using the multiple regression analysis continued by the partial correlation. The result of the multiple regressions indicates that HOTS, vocabulary mastery and reading motivation influence reading comprehension achievement with the F=236.709 with the significant level below 0.05 which means that the three independent variables influence significantly on reading comprehension achievement. The Adjusted R Square is 0.653 which means that the reading comprehension achievement is 65.3% predicted by the three independent variables. The contribution of HOTS on reading comprehension achievement is 38.7%, vocabulary mastery is 50.3%, and reading motivation is 8.2%.